Permanent relief from intermittent cold stress-induced fibromyalgia-like abnormal pain by repeated intrathecal administration of antidepressants - Mukae Takehiro; Araki Kohei; Nagai Jun; Uchida Hitoshi; Nishiyori Michiko; Kishioka Shiroh; Ueda Hiroshi (SAGE Publishing, 2011)
Abstract Background Fibromyalgia (FM) is characterized by chronic widespread pain, which is often refractory to conventional painkillers. Numerous clinical studies have demonstrated that antidepressants are effective in treating FM pain. We previously established a mouse model of FM-like pain, induced by intermittent cold stress (ICS). Results In this study, we find that ICS exposure causes a transient increase in plasma corticosterone concentration, but not in anxiety or depression-like behaviors. A single intrathecal injection of an antidepressant, such as milnacipran, amitriptyline, mianserin or paroxetine, had an acute analgesic effect on ICS-induced thermal hyperalgesia at post-stress day 1 in a dose-dependent manner. In addition, repeated daily antidepressant treatments during post-stress days 1-5 gradually reversed the reduction in thermal pain threshold, and this recovery was maintained for at least 7 days after the final treatment. In addition, relief from mechanical allodynia, induced by ICS exposure, was also observed at day 9 after the cessation of antidepressant treatment. In contrast, the intravenous administration of these antidepressants at conventional doses failed to provide relief. Conclusions These results suggest that the repetitive intrathecal administration of antidepressants permanently cures ICS-induced FM pain in mice.